African leadership : powerful paradigms for the 21st century - Elkington, Rob; Ngunjiri, Faith Wambura; Burgess, Gloria J.; Majola, Xoliswa; Schwella, Erwin; de Klerk, Nico (Emerald Publishing Limited, 2023)
African Leadership is an edited collection enriched by the people who have lived and experienced indigenous leadership first-hand, demonstrating how African leadership is distinctive from usual Western hegemonic paradigms. Providing an indepth discussion of the components, context, followers, and skills that contribute to the success of African leaders, African Leadership concludes with meaningful applications for 21st-century leaders globally.